Creative Writing and Intersemiotic Translation in the English Language Classroom: Turning Shapes and Colours into Flash Fiction - Barone, Linda (Margins/Marges/Margini, 2025)
This paper explores the integration of creative writing and intersemiotic translation as a multifaceted approach to English language learning. The translation between different semiotic systems (in this case from visual to textual), combined with creative writing, offers a rich pedagogical framework for engaging language learners in deep, meaningful interaction with the target language. The methodology employed a blended approach, incorporating Task-Based Language Teaching, Project-Based Learning, and learning by doing, wherein learners systematically progressed through a series of gradual activities designed to culminate in the composition of a concise narrative inspired by a visual artwork. Participants in the project were advanced-level students in their second year of the bachelor’s degree program in Foreign Languages and Cultures.Findings indicate that the students demonstrated significant improvement in both language proficiency and intercultural competence. Furthermore, the study found that these activities fostered a deeper emotional and cognitive engagement with the learning material, facilitating a more personal approach to language acquisition.Incorporating creative and multimodal approaches into the curriculum can lead to more effective and immersive language learning experiences. This study seeks to contribute to the growing body of literature on multimodal pedagogies and opens new avenues for exploring how creative writing and intersemiotic translation can be exploited to support language and linguistics learners in an increasingly interconnected and semiotically complex world.